1
$\begingroup$

After a long page of solving limits using l'Hôpital's rule only those 2 left that i cant manage to solve

$$\lim\limits_{x\to0}{\sqrt {\cos x} - \sqrt[3]{\cos x}\over \sin^2 x }$$

$$\lim\limits_{x\to\ {pi\over 2}}{\tan 3x - 3\over \tan x - 3 }$$

Thanks in advance for any help :)

i edit the second one in mistake i entered $0$ insted of $\pi\over 2$

$\endgroup$
  • $\begingroup$ Since $\tan x \to 0$ as $x \to 0$ the second one can be evaluated directly using continuity. $\endgroup$ – copper.hat May 23 '14 at 3:59
  • $\begingroup$ Second one isn't indeterminate form! $\endgroup$ – evil999man May 23 '14 at 4:01
  • $\begingroup$ For the first, note that $\sin^2 x = 1 -\cos^2 x$ and find the limit of ${ y^{1\over 2} - y^{ 1 \over 3} \over y^2 }$ as $y \to 1$ using l'Hôpital's rule. $\endgroup$ – copper.hat May 23 '14 at 4:03
2
$\begingroup$

$$\lim\limits_{x\to0}{\sqrt {\cos x} - \sqrt[3]{\cos x}\over \sin^2 x }=\lim\limits_{x\to0}{-\frac{1}{2}\sin x(\cos x)^{-\frac{1}{2}} + \frac{1}{3}\sin x (\cos x)^{-\frac{1}{3}}\over 2\sin x \cos x }=\lim\limits_{x\to0}{-\frac{1}{2}(\cos x)^{-\frac{1}{2}} + \frac{1}{3} (\cos x)^{-\frac{1}{3}}\over 2 \cos x }=-\frac{1}{12}$$

For the second one, you can evaluate the limit directly by substituting in $x=0$.

$\endgroup$
2
$\begingroup$

As $\displaystyle\sqrt{\cos x}-\sqrt[3]{\cos x}=(\cos x)^{\frac12}-(\cos x)^{\frac13}$ and gcd$\displaystyle\left(\frac12,\frac13\right)=\frac{\text{gcd}(1,1)}{\text{lcm}(2,3)}=\frac16,$

Set $\displaystyle\sqrt[6]{\cos x}=1+h\implies\cos x=(1+h)^6$

and $\displaystyle\sqrt{\cos x}-\sqrt[3]{\cos x}=(1+h)^3-(1+h)^2=(1+h)^2(1+h-1)$

Finally, $\displaystyle\sin^2x=1-(1+h)^{12}=-12h+O(h^2)$

$\endgroup$
  • $\begingroup$ very smart solution indeed !! $\endgroup$ – Paramanand Singh May 23 '14 at 18:37
  • $\begingroup$ @ParamanandSingh, Thanks for your feedback $\endgroup$ – lab bhattacharjee May 24 '14 at 12:26
0
$\begingroup$

@copper.hat thanks i think i got it

$$\lim\limits_{x\to0}{\sqrt {\cos x} - \sqrt[3]{\cos x}\over \sin^2 x } = \lim\limits_{x\to0}{\sqrt {\cos x} - \sqrt[3]{\cos x}\over 1-\cos^2 x } = \lim\limits_{y\to1}{\sqrt {y} - \sqrt[3]{y}\over 1- y^2 } $$ $$\lim\limits_{y\to1}{\sqrt {y} - \sqrt[3]{y}\over 1- y^2 } = \lim\limits_{y\to1}{\sqrt {y} - \sqrt[3]{y}\over 2y(6\sqrt[6] y) } = 0$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.